Reproductive toxicity of nanoscale graphene oxide in male mice. Issue 1 (February 2015) - Liang, Shanlu; Xu, Shun; Zhang, Ding; He, Junmin; Chu, Maoquan
Abstract In the past few years, much work has been performed to explore the biomedical applications and toxicity of nano-graphene and its derivatives. However, the reproductive toxicity of those carbon nanomaterials has been rarely studied. In this study, we report on the male reproductive toxicity of nanoscale graphene oxide (GO) using a mouse model. The results showed that the adult male mice injected with high dosages of GO (25 mg/kg mouse) via the tail vein exhibited normal sex hormone secretion and retained normal reproductive activity. All untreated female mice mated with the GO-treated male mice could produce healthy pups. There were no significant differences in pup numbers, sex ratio, weights, pup survival rates or pup growth over time between the GO-treated and control groups. Furthermore, these GO-treated male mice could produce a second, third, fourth and even fifth litter of healthy offspring when they lived with the untreated female mice. The testicular and epididymal histology as well as the activities of several important epididymal enzymes including α-glucosidase, lactate dehydrogenase, glutathione peroxidase and acid phosphatase were not affected by GO treatment. In addition, no damaging effects were seen at high dose rates of GO (total 300 mg/kg male mouse, 60 mg/kg every 24 h for 5 days) via intra-abdominal injection. Thus, GO showed very low or nearly no toxicity for male reproduction. This work will greatly enable future investigations of GO nanosheets for in vivo biomedical applications.